2020
DOI: 10.1002/jlb.5a0220-676rr
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo drug testing predicts chemosensitivity in acute myeloid leukemia

Abstract: The majority of acute myeloid leukemia (AML) patients will respond to standard chemotherapy, however, resistance is a prevalent problem contributing to incomplete responses, refractory disease, and ultimately patient death. Therefore, choosing more sensitive and effective chemotherapy regimens is of key clinical importance. In order to explore this issue, we investigated and optimized PharmaFlow, an automated flow cytometry method for evaluating the sensitivity of leukemia cells to multiple chemotherapeutic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Recently, Lin et al used the PharmaFlow method to examine bone marrow samples from 38 Chinese AML patients with a panel of 7 single drugs and 6 combinations with cytarabine at different concentrations. Their data suggested that ex-vivo drug activity strongly corresponded to clinical efficacy in Chinese AML patients (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lin et al used the PharmaFlow method to examine bone marrow samples from 38 Chinese AML patients with a panel of 7 single drugs and 6 combinations with cytarabine at different concentrations. Their data suggested that ex-vivo drug activity strongly corresponded to clinical efficacy in Chinese AML patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…The in-vitro single-cell culture methods such as 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and ATP assay cannot distinguish between tumor cells and non-tumor cells, or simulate the in-vivo microenvironment (8)(9)(10). Nowadays, high-throughput ex-vivo drug sensitivity screening test is used to detect pharmacological activity in the treatment of AML (11)(12)(13)(14)(15)(16)(17)(18). Herein, we tested the prediction value of the PharmaFlow platform using bone marrow samples of 104 AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have utilized high-throughput ex vivo testing of AML cells to functionally identify drug response patterns (18)(19)(20)(21)(22)(23)(24). The Beat AML study reported on the functional testing of 122 small molecule inhibitors combined with genomic profiling in a cohort of 562 biobanked AML patient samples (23).…”
Section: Introductionmentioning
confidence: 99%
“…Snijder et al applied an image-based drug testing assay (pharmacoscopy) to demonstrate that the assay predicted clinical response to chemotherapy (21). Flow-cytometry has also been used to quantify responses in distinct cell subpopulations (19,(25)(26)(27). Nevertheless, many of these studies are retrospective and lack the integration of functional and molecular data.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the different MOCs in each patient at each moment of their AML clinical history, that is, before, during and after treatment and relapse, would enable the use of personalized therapies with better results and less toxicity, which would result in a longer survival time. Some authors suggest that achieving this enterprise faces issues such as study costs and the technical limitations of molecular testing [ 45 ], others are more optimistic, recently a bone marrow mononuclear cell (BMMC) 3D culture model and an automated flow cytometry method, were tested to evaluating the sensitivity of leukemia cells to multiple chemotherapeutic drugs ex vivo and define resistance biomarkers of AML patient bone marrow samples in response to Ara-C treatment [ 46 , 47 ]. In silico analysis of highly prognostic human AML LSC gene expression signatures using existing datasets of drug-gene interactions have been used to identify compounds predicted to target LSC gene programs [ 48 ], the identification of a true genetic signature that predicts the response to cytarabine has been assayed in patients with AML through comprehensive multi-point analysis pharmacokinetic, pharmacodynamic (cytarabine-dependent) and clinical endings [ 49 ].…”
Section: Chemoresistance As Relapse and Refractory Diseasementioning
confidence: 99%